The effectiveness of vegetable oil formulations in reducing oviposition of Bactrocera dorsalis Hendel (Diptera: Tephritidae) in large red chili fruits - Hidayat, Yusup; Fauziaty, Muthia Riefka; Dono, Danar (Perhimpunan Entomologi Indonesia, 2018)
Chili peppers (Capsicum annuum), in their many varieties, constitute a culturally and economically important horticultural crop in a number of countries. The Indonesian cayenne large red chili (Capsicum annuum var. annuum) is used widely in Indonesia mainly in cooking. There have been reports of increased infestation of large red chili by insect pests, particularly fruit flies. The aim of this study was to investigate the effectiveness of five edible vegetable oils (palm oil, coconut oil, soybean oil, corn oil, and candlenut oil) and one non-edible vegetable oil (neem oil) in reducing landings, oviposition, and infestation by the Oriental fruit fly (Bactrocera dorsalis Hendel) in large red chili fruits. This lab-based experiment entailed exposure of large red chili fruits to 20 mature B. dorsalis females (14–21 days old) inside a 15-l plastic container. Six separate containers each held 10 large red chili fruits with a single oil treatment in each. Prior to exposure, each of the treated and control large red chili fruits was punctured once with a needle in order to create an opening for oviposition. Results indicate that the coconut oil formulation was most effective in preventing damage from B. dorsalis females, and reducing fruit fly landings, oviposition, and infestation.